Analisis Manajemen Risiko dengan Menggunakan Framework ISO 31000:2018 pada Sistem Informasi E-Gudang Satpol PP Kota Surabaya - Yolanda, Birgita; Nasrullah, Muhammad; Kusumawati, Aris (TeIKa, 2024)
The role of technology in today's business world is becoming increasingly important, especially in supporting the growth of companies or organizations. By optimizing Information Systems/Information Technology (IS/IT), institutions can enhance their competitiveness. However, the optimization of information technology assets also increases the risk that can threaten the achievement of company goals. Effective IS/IT risk management is crucial to maximizing the usefulness of information technology assets and improving business process efficiency. The Civil Service Police Unit (Satpol PP) requires good IS/IT risk management, particularly for the E-Gudang Information System used to manage Confiscated Goods (BHP). The risks of data loss, information leakage, and data input errors are challenges faced by Satpol PP in Surabaya. The E-Gudang Information System helps control BHP, manage inventory, and is integrated with other departments such as the public order and general affairs divisions. However, operational risks remain. Therefore, a comprehensive information technology risk management analysis is needed. The ISO 31000:2018 method is used to identify, assess, and manage these risks. ISO 31000:2018 provides guidelines for risk assessment, helping to evaluate the risk value of each identified risk. This study aims to minimize potential risks and provide recommendations to Satpol PP regarding risks in the E-Gudang Information System. The results of this study found 12 potential risk threats, including 2 with a high level, 9 with a medium level, and 1 with a low level.